2017
DOI: 10.3389/fmicb.2017.01665
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-Based Assay Targeting the Major Capsid Protein Gene of a Dinorna-Like ssRNA Virus That Infects Coral Photosymbionts

Abstract: The coral-Symbiodinium association is a critical component of coral reefs as it is the main primary producer and builds the reef's 3-dimensional structure. A breakdown of this endosymbiosis causes a loss of the dinoflagellate photosymbiont, Symbiodinium, and/or its photosynthetic pigments from the coral tissues (i.e., coral bleaching), and can lead to coral mortality. Coral bleaching has mostly been attributed to environmental stressors, and in some cases to bacterial infection. Viral lysis of Symbiodinium has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 62 publications
(84 reference statements)
3
39
0
Order By: Relevance
“…The 124 unique dinoRNAV aminotypes (Figure 2; Table S1) identified in this study were most similar to 13 amino acid sequences from a previously published dinoRNAV library (28); sequence similarities to aminotypes from published dinoRNAVs ranged from 52.1-99.3% (e- values ranged between 9.6·10 -73 -2.7·10 -35 , Table S1). All dinoRNAV mcp aminotypes in this study form a clade that is more recently derived than reference sequences such as HcRNAV, Beihai sobemo-like virus and sponge weivirus-like virus (Figure 2).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The 124 unique dinoRNAV aminotypes (Figure 2; Table S1) identified in this study were most similar to 13 amino acid sequences from a previously published dinoRNAV library (28); sequence similarities to aminotypes from published dinoRNAVs ranged from 52.1-99.3% (e- values ranged between 9.6·10 -73 -2.7·10 -35 , Table S1). All dinoRNAV mcp aminotypes in this study form a clade that is more recently derived than reference sequences such as HcRNAV, Beihai sobemo-like virus and sponge weivirus-like virus (Figure 2).…”
Section: Resultssupporting
confidence: 62%
“…Recent surveys of free-living marine microbial communities reported that viral infections may occur in ∼33% (66, 67) to over 60% (68) of marine microorganisms, and many individual cells may be infected by several viruses at a given time (66, 69). Considering that our sequencing data are based on mcp gene amplicons from RNA libraries generated from unfractionated coral tissue, dinoRNAV mcp gene detections could potentially arise from several sources, including RNA genomes within intact dinoRNAV capsids (28), mcp genes that are being expressed in host cells during the dinoRNAV replication cycle, free dinoRNAV genomes that may occur as extrachromosomal RNA in a latent (25) or carrier state similar to pseudolysogeny (70, 71), and/or expressed endogenized viral elements in host genomes (72, 73). The amplicon sequencing approach employed here limits our ability to discern amongst these potential sources of viral mcp gene detections, as does the dearth of information available on dinoRNAV replication cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Symbiodiniaceae + ssRNA virus that infects and kills algal symbionts in culture has been described based on genomic analysis (Correa et al, 2012;Levin et al, 2017), but to date no images of these viruses have been published. Members of the + ssRNA viruses that infect free-living dinoflagellates such as Heterocapsa circularisquama (HcRNAv) are similarly shaped and have capsids in the 40 nm size range of those observed within the bleaching corals here (Tomaru et al, 2004;Lawrence et al, 2014;Montalvo-Proaño et al, 2017;Weynberg et al, 2017). Thus, we speculate that these viruses may be small RNA viruses associated with the bleaching event.…”
Section: Microscopy Indicates Corals Are Infected With Multiple Eukarmentioning
confidence: 92%
“…Transcripts of the ssRNA virus were shown to be present at high abundance in a heat-sensitive Symbiodinium culture, while they were barely detectable in a conspecific heat-tolerant culture, suggesting Symbiodinium and perhaps coral thermal tolerance is linked to the presence of this virus 19 . In order to progress the research in the field, PCR primers have been designed to assess presence and diversity of the ssRNA virus; these primers can potentially be modified for virus quantification during in situ coral bleaching events 20 .…”
Section: Eukaryotic Viruses In Coral Disease and Bleachingmentioning
confidence: 99%